2005
DOI: 10.1007/s00381-005-1161-1
|View full text |Cite
|
Sign up to set email alerts
|

Cystic spinal dysraphism of the cervical and upper thoracic region

Abstract: Cystic dysraphisms of the cervical and upper thoracic region differ clinically and structurally from meningomyelocele and have a more favorable outcome. We believe that these malformations have not been properly labeled and propose a classification based on the structures found inside the cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 39 publications
3
62
0
4
Order By: Relevance
“…The authors state that "only 15 cases so far have been reported throughout the literature." In 2006, we reported three cases of myelocystoceles (MCC) in a series of 18 patients with cystic dysraphisms of the cervical and upper thoracic region (CDCT) [2], and our paper was not mentioned by the authors. In our report, we found it reasonable to group the lesions according to the findings inside the cyst due to the many controversies concerning how to label them properly.…”
Section: Dear Editormentioning
confidence: 91%
See 2 more Smart Citations
“…The authors state that "only 15 cases so far have been reported throughout the literature." In 2006, we reported three cases of myelocystoceles (MCC) in a series of 18 patients with cystic dysraphisms of the cervical and upper thoracic region (CDCT) [2], and our paper was not mentioned by the authors. In our report, we found it reasonable to group the lesions according to the findings inside the cyst due to the many controversies concerning how to label them properly.…”
Section: Dear Editormentioning
confidence: 91%
“…Although stalks and MCC may share a common embryogenesis as proposed by Steinbok and Cochrane [4], in our judgment, neuroglial stalks are not MCC. While in MCC the sac is lined by ependyma, stalks are composed of glioneural elements, blood vessels, meningoepithelial cells, and sometimes, only of fibroconnective tissue and blood vessels [2,4,5]. Therefore, if stalks (Rossi's group A) were to be considered as MCC, our casuistic would certainly be much more expressive.…”
Section: Dear Editormentioning
confidence: 97%
See 1 more Smart Citation
“…1,2 Same author classified the lesion into 3 types -type I -a fibrovascular or neuroglial tissue protruding from posterior surface of spinal cord attach to the sac wall, type II -an ependymal-lined cyst that herniates inside of a meningocele, representing a hydromyelic canal in connection with an outer cyst and type-III true meningoceles in which meningeal tissue herniates through the defect and the sac contains only CSF. 2 Type 1 is commonly seen and can be associated with tethered cord. Other associated anomalies include hydrocephalus, Chiari malformations, hydromyelia, diastematomyelia, thickened filum terminal and KlippelFeil syndrome.…”
Section: Incidencementioning
confidence: 99%
“…14) This lesion is typically observed in the cervical, cervicothoracic, and thoracic regions and is often associated with some anomaly such as Chiari type II malformation and hydrocephalus. 1,4,6,[9][10][11]13,17) Plastic repair of the sac with adequate untethering has been recommended for cervical (non-terminal) myelocystocele. 9,10,13) However, respiratory distress after sac closure has been reported in a few cases, requiring immediate placement of ventriculoperitoneal (VP) shunt to prevent rapid deterioration of associated hydrocephalus and Chiari type II malformation.…”
Section: Introductionmentioning
confidence: 99%